PENERAPAN METHODOLOGY FOR PARTICIPATORY ASSESSMENT (MPA) DALAM MENGENALI POTENSI PEMBERDAYAAN MASYARAKAT KAMPUNG TANJUNG MANGGU, DESA SIMPANG, WANAYASA - Siti Napsiyah; Elisa Nur Faizah; Intan Nurmaisya; Puteri Indah Maharani; Siti Nurhaliza (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Researchers introduce participatory methods to help communities carry out further analysis and planning through the MPA or PRA method. Through participatory action research, the method used prioritizes active community participation with the researchers help as facilitators for community to realize designing and using participatory methods to conduct potential assessments which will later become a conceptual form in rural area development in the idea of the Tanjung Manggu Village community empowerment program, Desa Simpang, Kecamatan Wanayasa. This research was conducted to analyze the success of implementing MPA as a way to help the people of Tanjung Manggu Village carry out experiments to determine the potential and conditions that exist in their environment in order to improve the life quality of the people in the area. The study method used is a qualitative approach with Participatory Action Research (PAR) techniques. The results of this research show that recognizing the potential for community empowerment can be applied through Participatory Rural Appraisal (PRA), Methodology for Participatory Assessment (MPA), and using the help of the Self Esteem, Associate Strength, Resourcefulness, Action Planning, and Responsibility (SARAR) approach can be implemented so as to produce a program design to grow potentials that can be empowered. This is proven by the interest of young people in Tanjung Manggu who have leadership qualities and potential successors to the previous leadership who have become Karang Taruna. Apart from that, there are also young people from the Tanjung Manggu community who focus on developing businesses in the agricultural sector, expertise in managing Home Industry, namely tea which is produced on a small scale, making palm sugar which is still produced on a small scale, and making finding fish with a medium marketing scale